Desain Prototype Aplikasi Pencatatan Korban Bencana Pendukung Mitigasi Bencana di Kabupaten Jember - Vanny Permata Sari; Feby Erawantini; Rinda Nurul Karimah; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
18 of 31 sub-districts in Jember Regency are areas prone to floods, landslides, tornadoes and tsunamis.The number of disasters resulted in the difficulty of officers to record the number of victims that exist and thedelivery of information related to disaster data, needs in the area of the disaster and so forth is difficult toconvey. This research was aimed to design a prototype application for recording disaster victims to help thelocal government of Jember specifically for supporting disaster mitigation. The method applied in this studywith 2 stages, namely the first stage to analyze the problems and system design needs, researchers relatedto the collection of necessary data such as retrieving data on disaster victims in Jember Regency andlegislation related to application users and the second stage doing system design such as making flow andmodeling of disaster victim registration applications that provide solutions to problems in the scope of usingavailable resources. Data collection techniques are interviews, observation and documentation withqualitative data analysis methods. The results of this study are prototype design of web-based disasterregistration applications that are designed according to user needs using Microsoft Visio applications. Theresults of the design of the prototype design are expected to be a reference for web-based disasterregistration application specifications in the Jember Regency government environment.